Daredevil by chip zdarsky, volume 7 ebook Lockdown. - Zdarsky, Chip (Daredevil (2019), 2022)
Collects Daredevil (2019) #31-36. The Angel of Death has come to Hell's Kitchen. As a series of grisly murders tests Elektra's mettle — and her commitment to her role as the new Daredevil — the city spirals into a state of panic. With the body count mounting, even the Marvel Universe's deadliest assassin is at somewhat of a loss — because this serial killer can be in more than one place at a time! A team? A mutant? Or something else entirely? Meanwhile, Matt Murdock faces challenges of his own behind bars after being exposed to a dangerous and experimental compound that makes subjects more aggressive and violent. Whatever happens, one thing is certain: Matt won't be getting time off for good behavior! The next installment of Chip Zdarsky's Eisner Award-nominated run delivers twists, turns and unexpected allies!